A three dimensional human amniotic membrane/fibrin scaffold for cartilage tissue engineering application / Iklil Hakimah Hussin - Iklil Hakimah, Hussin (2017)
In engineering a cartilage tissue, the survival of the chondrocytes is directly interdependent to the extracellular matrix production. Therefore, the choice of biomaterials for cartilage tissue engineering application is crucial in determining the survival of the chondrocytes. Natural biomaterials pose great advantages for tissue engineering applications due to their biocompatibility, biodegradability and ease of availability. These materials are not only sustainable but pose a lower risk of rejection by the body. Human Amniotic Membrane (HAM), for example, is a 2 dimensional (2D) biocompatible and biodegradable material. The main objective of this study is to develop a 3 dimensional (3D) scaffold made from HAM a well-known natural biomaterial to supports chondrocytes proliferation and matrix production with an ultimate aim to promote tissue regeneration in cartilage tissue engineering application. This thesis presents the development of a novel 3D HAM/ Fibrin scaffold that was produced from a crosslink of HAM extracts and fibrin to form a stable scaffold to ensure uniform cell dispersion throughout the scaffold. This thesis also outlines the parameters that validate the feasibility of the scaffold following the success of optimization of the developed 3D HAM/ Fibrin scaffold (1:1 (v/v) ratio of HAM/ Fibrin with a concentration of 5 million cells/ml set within 30 minutes). The results of total DNA and GAG content production of this novel scaffold supports the cartilage matrix production and cell survival in vitro. Predominantly, chondrocytes favoured the HAM/ Fibrin scaffold as results for both DNA and GAG content recorded a significant increase than the control group. Moreover, the histological evaluation also revealed chondrocytes favouring HAM/ Fibrin scaffold when it comes to proteoglycans synthesis which further supports the result from the DNA and GAG content production. The FESEM evaluation also affirms the DNA and GAG content production favouring HAM/ Fibrin scaffold with apparent signs of cell-cell connection, cell-ECM adhesion and cytoskeletal filaments. This study is a step forward in scaffold fabrication for cartilage tissue engineering as it is a known fact that HAM constituents are quite similar to native cartilage and the results from this study further support the use of natural biomaterial in mimicking the native microenvironment of the intended tissue replacement.